THERMAL COMFORT STUDY IN CONVERTING PROCESS OF PLASTICS MANUFACTURING INDUSTRY - Sugiono Sugiono; Oyong Novareza; Ryan Fardian (Journal of Environmental Engineering and Sustainable Technology, 2016)
Thermal comfort is one of environment factors that can have a significant impact on workers performance. For a better thermal comfort, several factors that affect thermal conditions should be considered. Air temperature is a factor that give significant effect on thermal conditions. This paper is study about thermal comfort in a building for converting process at plastics manufacturing industry located in Malang. During the day, temperature on that building can reach as high as 36 °C. CFD (Computational Fluid Dynamics) simulations is use to determine the air properties inside the building. Thermal comfort experienced by workers through this study was based on PMV (Predicted Mean Vote) model and PPD (Predicted Percentage of Dissatisfied) model. The result of this study shows that thermal comfort in building of converting process can be increased by reduced heat sources on that building. Thermal comfort can be said increased when PMV and PPD value are decreased. After improvement recommendations is given, the PMV value for existing conditions in range 1.83 to 2.82 is decreased into range 1.63 to 2.18, while the PPD value for existing conditions in range 68.9% to 98% is decreased into range 58.2% to 84.2%.